Maximal isokinetic peak torque and EMG activity determined by shorter ranges of motion - Oliveira, Anderson [UNESP]; Corvino, Rogério [UNESP]; Gonçalves, Mauro; Caputo, Fabrizio [UNESP]; Denadai, Benedito [UNESP] (Termedia Sp. z.o.o., 2012)
Purpose. Isokinetic tests are often applied to assess muscular strength and EMG activity, however the specific ranges of motion used in testing (fully flexed or extended positions) might be constrictive and/or be painful for patients with injuries or under-going rehabilitation. The aim of this study was to examine the effects of different ranges of motion (RoM) when determining maximal EMG during isokinetic knee flexion and extension with different types of contractions and velocities. Methods. Eighteen males had EMG activity recorded on the vastus lateralis, vastus medialis, semitendinosus and biceps femoris muscles during five maximal isokinetic concentric and eccentric contractions for the knee flexors and extensors at 60° • s -1 and 180° • s -1. The root mean square of EMG was calculated at three different ranges of motion: (1) a full range of motion (90°-20° [0° = full knee extension]); (2) a range of motion of 20° (between 60°-80° and 40°-60° for knee extension and flexion, respectively) and (3) at a 10° interval around the angle where peak torque is produced. EMG measurements were statistically analyzed (ANOVA) to test for the range of motion, contraction velocity and contraction speed effects. Coefficients of variation and Pearson's correlation coefficients were also calculated among the ranges of motion. Results. Predominantly similar (p > 0.05) and well-correlated EMG results (r > 0.7, p ≤ 0.001) were found among the ranges of motion. However, a lower coefficient of variation was found for the full range of motion, while the 10° interval around peak torque at 180° • s -1 had the highest coefficient, regardless of the type of contraction. Conclusions. Shorter ranges of motion at around the peak torque angle provides a reliable indicator when recording EMG activity during maximal isokinetic parameters. It may provide a safer alternative when testing patients with injuries or undergoing rehabilitation.
Keywords: concentric; eccentric; joint angle; knee extension; torque